Enhancing African orphan crops with genomics - Jamnadass, Ramni H.; Mumm, R.H.; Hale, I.; Hendre, P.; Muchugi, A.; Dawson, Ian K.; Powell, W.; Graudal, Lars; Yana-Shapiro, H.; Simons, A.J.; Deynze, A. van (Springer, 2020)
The African Orphan Crops Consortium promotes the strategic, genome-enabled improvement of under-researched crops for biodiversity-based, nutritious food solutions in Africa. The African Plant Breeding Academy empowers the continent’s plant breeders to apply advanced genetic approaches and shared genetic solutions to the task of tailoring the immense diversity of underutilized crops to the needs of Africa’s producers, processors and consumers.